EVIDENCE-BASED TEACHING STRATEGY - Rommel Pascual Manzon, (EPRA International Journal of Research and Development (IJRD), 2022)
Most teachers care about their students' results, and if you are reading this article, you are undoubtedly one of them. Be supported by hard research, instead of anecdotal case studies or untested theories. Have a substantially higher effect on student results than other teaching strategies. Be able to be used on a wide range of subjects and at every year level. What evidence-based teaching strategies made it onto the list? Research shows that evidence-based teaching strategies are likely to have the largest impact on student results performance. Research shows that a few of these teaching strategies, such as holding high expectations of students, have a significant positive impact on student results. Do not assume that a teaching strategy is no good just because it is not in the top 10 or commonly used by teachers. That said, some popular teaching strategies do not have a large effect on student results. Once you are clear about what you want your students to know and be able to do by the end of the lesson, you need to tell them what they need to know and show them how to do the tasks you want them to be able to do. Some evidence-based teaching strategies that did not make the top 10 or are commonly used by teachers are still worth adopting. However, when you explore the thousands of research studies on the topic, it is apparent that some teaching strategies have far more impact than other teaching strategies do.